Heterogeneous reactive extraction for isopropyl alcohol liquid phase synthesis: Microkinetics and equilibria. (22nd November 2016) - Walter, Vanessa; Pfeuffer, Bernhard; Hoffmann, Ulrich; Turek, Thomas; Hoell, Detlef; Kunz, Ulrich
Abstract: The reaction kinetics for the liquid phase synthesis of isopropyl alcohol (IPA) from propene (P) and water (W) using a macroporous sulfonic acid ion exchange resin as catalyst were determined experimentally in a multiphase CSTR in the temperature range 398 K to 433 K at 8 MPa. This high pressure is necessary to dissolve propene in the aqueous phase and to ensure a liquid or supercritical state of all components. At typical reaction conditions, the reactants form two immiscible phases; the reaction takes place in the water swollen gel phase of the catalysts microspheres. Due to the large excess of water in the gel phase the compositions in the gel phase, in the macropore fluid, and in the catalyst surrounding aqueous phase are assumed to be identical. For temperatures up to 413 K the reaction kinetics for the used catalyst size are not influenced by mass transfer resistances within the catalyst matrix. Two reactions, the formation of IPA and the condensation reaction of two IPA molecules forming the by-product diisopropyl ether (DIPE), are investigated. The experimental results can be described sufficiently by pseudo-homogeneous rate expressions in aqueous phase activities. For the formation of IPA, the forward reaction is first-order in propene and water while the reverse reaction is first-order in IPA. The activation energy of the forward reaction was determined to 115.3 kJ/mol. The formation of DIPE is second order with respect to the activity of IPA. The reverse reaction is first order with respect to the activities of DIPE and water. The activation energy was determined to 85.6 kJ/mol. Simultaneous chemical and phase equilibria were investigated theoretically using the volume translated Peng-Robinson equation of state (VTPR-EoS) in combination with a g E -mixing rule. Parameters of the used g E -model were adjusted to experimental liquid-liquid equilibrium (LLE) data.